The Cupper Therapy Effectiveness on Reducing Cholesterol in Hamdalah Ruqyah and Bekam Syar'iyyah Clinic - Arlia, Arlia; sudarman, sudarman; Alam , Rizqy Iftitah (Devotion: Journal of Community Service, 2022)
High blood cholesterol levels are a health problem that continues to occur to anyone who does not follow a healthy lifestyle. The impact of high cholesterol levels in the blood is a big risk for heart disease. In addition to treatment using pharmacological treatment, namely with complementary management is cupping. This study aims to determine the effectiveness of cupping therapy on reducing high cholesterol levels at Hamdalah Ruqyah Clinic and Syar Cupping, Iyyah Makassar. This type of research is a quantitative research, with a pre-experimental research design in the form of One Group pre-test-post-test design. The determination of the sample in this study used a non-probability sampling technique with purposive sampling type with a sample size of 10 respondents. The statistical test used in this study was the Wilcoxon non-parametric test. The results showed that there was an effect of cupping therapy on reducing cholesterol levels with p value = 0.005. The conclusion of this study is cupping therapy is effective in lowering cholesterol levels.